4(3k-7)-5=11+k

Simple and best practice solution for 4(3k-7)-5=11+k equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(3k-7)-5=11+k equation:



4(3k-7)-5=11+k
We move all terms to the left:
4(3k-7)-5-(11+k)=0
We add all the numbers together, and all the variables
4(3k-7)-(k+11)-5=0
We multiply parentheses
12k-(k+11)-28-5=0
We get rid of parentheses
12k-k-11-28-5=0
We add all the numbers together, and all the variables
11k-44=0
We move all terms containing k to the left, all other terms to the right
11k=44
k=44/11
k=4

See similar equations:

| 7x+5-x=6x+5 | | (8x-5)+65=180 | | -2n-8n=-13+7-n-3n | | 6(8m-4)=-24-4m | | 3y+8-y=8+y+5 | | 5/6=x-2/x | | 3+x=-103 | | -2-8=3x+7 | | v+v=2 | | 39+-x=1 | | (7x+1)=(10x-9) | | 1.2m+6=-10 | | 3-x+3x=17 | | 25n+7=18n+28 | | (7x+1)=10x-9) | | 5(3x-2)-7=28 | | 3-8x=72 | | -6(1-3x)=-6(-x+7) | | 5+5x=8x-20 | | t=5;t+38 | | 3-8x=80 | | (19x-18)=(10x-9) | | p=8+6+8+(1/2(2)3.14)(3) | | 3r+3/6=3r-6/3 | | 6–7f=-1–8f | | k-(9)/3=11 | | -4(w+7)=-7w-10 | | (19x-18)=10x-9) | | k-(9/3)=11 | | 7v+1=5(v-3) | | 8=3y-20=52 | | t=5;,t+38 |

Equations solver categories